'And our Muhammad goes with the Archangel Gabriel to Choir': Sixteenth-Century German Accounts of Life under the Turks*. (January 2015) - Methuen, Charlotte
Abstract : In the German lands of the sixteenth century, the threat of Turkish invasion coloured perceptions of religious diversity. As the Turkish threat became more real to Western Europeans, the experiences of Christians under the Turks, and the responses of the Turks - who were of course Muslims - to encounters with the Christian faith became topics of considerable concern. In 1539, a pamphlet purporting to offer a German translation of a letter from Constantinople was printed in Augsburg, Magdeburg and possibly Nuremberg.